The fos homolog kayak is required for adult eye formation and function in Drosophila. - Zúniga-García, M.; Riesgo-Escovar, J.R. (Frontiers in neuroscience, 2025)
This study characterizes the requirements of the kayak (kay) gene in Drosophila melanogaster adult eye biology by examining mutant phenotypes in photoreceptor development, external eye morphology, corneal and bristle ultrastructure, and visually guided behaviors, such as phototaxis, in kay strong loss-of-function homozygous mutant clones. Despite previous studies on kay, there is a dearth of phenotypic characterization of the morphological and behavioral consequences of kay loss-of-function alleles in the adult eye. We find that kay is expressed in developing ommatidia in eye discs. The kay mutant ommatidia are misaligned, lack photoreceptors, have malformed corneal surfaces, and have misshaped, misplaced, and fewer mechanosensory bristles. Corneal nipples, while present in mutant corneas on the corneal surface, are disorganized and malformed. With an average of 30% of the eye territory mutant, flies have a significantly lower response in a behavioral phototaxis assay. Altogether, kay function is required for multiple cell types in the adult retina, and this stands in stark contrast with other jun kinase genes, like the fly homologs of jun kinase and jun, genes not required for adult eye morphogenesis. This is consistent with Kayak functions that are independent of heterodimerizing with Jun proteins or requiring activation of the jun kinase pathway.